PENGARUH UKURAN PERUSAHAAN DAN DEBT TO EQUITY RATIO ATAS NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING - Nur Syafitri Siregar (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
The studies show that size of company has profitability effect. DER (Debt to equity ratio) affects profitability. The firm size affects the firm value. Debt to equity ratio affects the firm value. Profitability affects the firm value. The firm size affects the firm value in the consumer goods industry companies listed on the Indonesia Stock Exchange with profitability as a mediating variable. Debt to equity ratio affects the firm value in consumer goods industry companies listed on the Indonesia Stock Exchange with profitability as a mediating variable.